Time and behaviour : psychological and neurobehavioural analyses - Bradshaw, C. M. (Christopher M.); Szabadi, E. (Elmer) (Advances in psychology (Amsterdam, Netherlands), 1997)
That time is both a dimension of behaviour and a ubiquitous controlling variable in the lives of all living things has been well recognized for many years. The last decade has seen a burgeoning of interest in the quantitative analysis of timing behaviour, and progress during the last five or six years has been particularly impressive, with the publication of several major new theoretical contributions. There has also been considerable progress in behavioural methodology during the past decade. In the area of reinforcement schedules, for example, the venerable interresponse-time schedule, fixed-interval peak procedure and interval bisection task have been complemented by a 'second generation' of incisive instruments for analyzing timing behaviour. Another area of recent development is the analysis of the neurobiological substrate of timing behaviour. Several research groups are currently studying the involvement of various central neurotransmitter systems in the timing behaviour, and the ability of centrally acting drugs and discrete brain lesions to alter timing processes. Yet another recent development in timing research is the growing dialogue between two fields that have grown up separately, although, superficially at least, they seem to have much in common: the experimental analysis of 'interval timing', traditionally the province of experimental psychology, and behavioural chronobiology. The last few years have seen a growing interest in the comparative properties of the internal 'clocks' that regulate biobehavioural rhythms with time bases in the circadian range or longer, and those that are entailed in timing of intervals in the range of seconds or minutes. All these areas of research, and others, are represented in the chapters that make up this volume. This book will help to promote further interactions among researchers who hail from disparate disciplines, but who share a common interest in the temporal properties of behaviour.